Personal Liability Insurance - Bak, Joanna (Olsztyn Economic Journal, 2012)
Personal liability insurance is still not popular as a way to cover accidental injury or damage to the property of a third party. The aim of the conducted research was to identify the limit of coverage and popularity of personal liability insurance on the Polish insurance market. This article presents the number of insurers offering personal liability insurance, the number of policies and the gross written premiums from 2004 until 2009. In depth analysis of the personal liability insurance, general conditions was conducted and the popularity of personal liability insurance among the employees of the Marshal’s Office in Olsztyn was surveyed.